PERENCANAAN DAN PEMBUATAN ALAT PENGUPAS KULIT JAGUNG - Sulaiman, Sulaiman; Aprilianto, Karolus (ITP Press, 2024)
Food crop commodities are the dominant commodities and are developed intensively, especially corn. After the corn is harvested, it is necessary to take several handling steps, one of which is by peeling the skin and shelling corn, previously farmers carried out the process of peeling the skin and picking corn manually which requires a lot of labor and costs and a long time. This causes very little yield, and not infrequently a lot of corn is of poor quality due to ineffective processing. From the existing problems, the author designed and made a combination of peeling machine and corn sheller. The design of the corn peeler and sheller uses an electric motor with a capacity of 0.5 HP as a drive. From the test results of the corn peeler and sheller machine, trials were carried out three times with a period of 2 kg, 3 kg, and 4 kg of corn that was still intact with skin. After the corn has been weighed, the corn is then put into the corn peeler and sheller machine with different treatments, namely putting corn into the machine one by one with pauses, inserting corn one by one, and the third trial is inserting corn one by one without pause, so that the average time produced is 1 minute 6 seconds from the peeling and picking process.